Research productivity: Trend and comparative analyses by regions and continents - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Using data for the period 2000 to 2019, the aim of this paper is to: (i) profile and compare research publications in regions and continents worldwide namely Africa, Western Europe, Eastern Europe, Northern America, Latin America, the Asiatic region, the Pacific region and the Middle East; (ii) assess factors associated with research productivity and (iii) verify if African countries are closing the deep gap of research production and by extension, detect factors on which to improve and boost the catch-up process. The empirical evidence is based on the Poisson regression model, quantile regression for counts data and panel negative binomial regression. The findings can be summarised as follows: (i) continuous and linear increasing trends in the production of knowledge are noted in developing regions specifically in Africa even if the contribution of the continent to global research is marginal; (ii) in countries with least production, 'internet users' is not significant but schooling modulates its effect on research production contrarily to countries in the upper part of the distribution and (iii) in Africa, if the number of schooling years increases by one, the number of documents or published works produced is expected to increase by a factor of 1.147.
Keywords: F42; O10; O30; O38; O57; 330; Research productivity; economic development; count data